Diversity in Facilitation: Mapping Differences in Deliberative Designs - Daniel Oppold; Dirk von Schneidemesser; Dorota Stasiak (Journal of Deliberative Democracy)
There are various approaches to facilitation in deliberative mini-publics, yet the scholarly literature remains relatively underdeveloped in identifying which approaches to facilitation are useful in achieving certain deliberative goals. This article compares facilitation approaches based on their potential to achieve different deliberative goals by examining three cases of deliberative mini-publics on urban transformations in the German city of Magdeburg. All three mini-publics were given the same task but were implemented using a particular approach to facilitation: (1) self-organized; (2) a multi-method approach; and (3) dynamic facilitation. We analyzed video recordings and surveys conducted among participants and found that differences in facilitation influence the process of deliberation in numerous ways. While deliberation can happen without a facilitator, certain deliberative goals can be better achieved when the process is professionally facilitated. More stringent or involved facilitation, however, may not serve every purpose of deliberation equally. There are trade-offs when designing, convening, or facilitating deliberative processes, and no approach fits all mini-publics. We conclude the article by identifying the implications of our findings for the scholarship and practice of citizen deliberation in structured forums and beyond.